4. SUPERIOTAS NEGARA ATAS ORGANISASI INTERNASIONAL: KEGAGALAN KERJA SAMA UNODC – MYANMAR DALAM MENANGANI PRODUKSI OPIUM PERIODE 2006-2013 - Medyna Oktavia; Hermini Susiatiningsih; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Myanmar is the second biggest producer of opium in the world after Afghanistan. Opiumproduction in Myanmar is taking place in Golden Triangle region where is vulnerable topoverty and armed conflict. Although poppy cultivation and opium production has beendeclared illegal by the Government through Act of 1974, most society still commit thecrime. On the other hand, UNODC has established cooperation with Myanmar since 2002but failed to reduce the number of opium production. The cooperation has resulted inseveral policies such as International Crop Monitoring Program and AlternativeDevelopment. Implementation of these policies lose ground due to the increase in opiumproduction. This study tries to analyze the causes of the failure of cooperation using realistapproach combined with evaluative framework borrowed from public administration. Thisstudy argues that UNODC has no bargaining power towards Myanmar so it failed to forceMyanmar comply the agreement. In addition, the failure also caused by conflict of interestbetween both parties while in implementing the agreement.